2010
DOI: 10.1161/atvbaha.110.215459
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of an Active Form of Vitamin D 3 (Calcitriol) Decreases Atherosclerosis in Mice by Inducing Regulatory T Cells and Immature Dendritic Cells With Tolerogenic Functions

Abstract: Objective-To determine whether the administration of an active form of vitamin D 3 (calcitriol) could prevent atherosclerosis through anti-inflammatory actions. Methods and Results-Recent clinical studies have shown that lack of vitamin D 3 is a risk factor for cardiovascular events.Oral calcitriol administration decreased atherosclerotic lesions, macrophage accumulation, and CD4 ϩ T-cell infiltration at the aortic sinus, when compared with the corresponding observations in control mice. We observed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(137 citation statements)
references
References 35 publications
9
125
0
3
Order By: Relevance
“…The active form of vitamin D3, 1, 25(OH)2-dihydroxyvitamin D3 (calcitriol), and its analogue inhibited autoimmune disease in animal models via inducing tolerogenic DCs and Tregs [20][21][22][23] . Similar to these studies, for the first time, we demonstrated the beneficial effects of orally administrated calcitriol on atherosclerosis in apolipoprotein E-knockout (ApoE −/− ) mice by inducing Tregs and tolerogenic DCs 24) . Considering the strategy to prevent atherosclerosis by inducing Tregs and tolerogenic DCs, our group has focused on the intestinal immune system as a therapeutic target.…”
Section: Mature Phenotypes Of Cdcs (Cd83supporting
confidence: 68%
See 2 more Smart Citations
“…The active form of vitamin D3, 1, 25(OH)2-dihydroxyvitamin D3 (calcitriol), and its analogue inhibited autoimmune disease in animal models via inducing tolerogenic DCs and Tregs [20][21][22][23] . Similar to these studies, for the first time, we demonstrated the beneficial effects of orally administrated calcitriol on atherosclerosis in apolipoprotein E-knockout (ApoE −/− ) mice by inducing Tregs and tolerogenic DCs 24) . Considering the strategy to prevent atherosclerosis by inducing Tregs and tolerogenic DCs, our group has focused on the intestinal immune system as a therapeutic target.…”
Section: Mature Phenotypes Of Cdcs (Cd83supporting
confidence: 68%
“…Importantly, this dose did not affect calcium metabolism in our study. A significant increase in CD4 + T cells within plaques, compared with the control group 24) . Interestingly, immunohistochemical analyses of atherosclerotic lesions indicated a significantly increased number of Foxp3 + Tregs and decreased number of CD11c +…”
Section: Oral Immune Modulation By Calcitriol Could Be Used As a Prommentioning
confidence: 86%
See 1 more Smart Citation
“…108 The (1,25-dihydroxycholecalciferol), an active form of vitamin D3, 124 and vaccination) limit inflammation and the development of atherosclerosis.…”
Section: Targeting Effector T Cell Responsesmentioning
confidence: 99%
“…Oral administration of the active form of vitamin D3 (calcitriol) was found to induce tolerogenic DCs and Treg cells, leading to the attenuation of atherosclerosis in mice (Takeda et al, 2010). In addition, the administration of DCs pulsed with oxidized low density lipoprotein (LDL) to mice deficient in LDL receptors reduced atherosclerosis and increased plaque stability (Habets et al, 2010).…”
Section: Harnessing Dendritic Cells As a Therapeutic Target In Atheromentioning
confidence: 99%